PERANCANGAN SISTEM MONITORING AIR KOLAM BERBASIS ANDROID MENGGUNAKAN METODE EXTEREME PROGRAMMING - Maulana , Haisyam; Nurlina, Tita; Permana, Nana Yudi (Universitas Majalengka, 2025)
Tilapia cultivation in Kampung Nila Kawali relies heavily on air quality as a key success factor. Currently, air quality monitoring is still done manually, resulting in inaccurate results, especially with a large number of ponds and extensive cultivation areas. This study aims to design an integrated pond quality monitoring and maintenance system tailored to user needs. The system was developed using the Extreme Programming (XP) method, with stages of planning, design, coding, and testing. This method was chosen because it is flexible to changing needs, accelerates development, and improves communication between developers and users. The design results indicate that the system successfully meets user needs in terms of interface and features. The system can display information on air quality parameters, pond locations, maintenance schedules, and air quality history in a concise and easy-to-understand manner. A warning notification feature is also designed to provide immediate information when air quality parameters are outside normal limits or require maintenance action.